Characteristics Of Kaolin From Eastern Kinta Valley And Its Potential For Industrial Uses - Khong, Ling Han (2018)
Kaolin is a mineral resource which exhibits highly variable properties when found in nature due to the differences in geological context at the location they formed. All kaolin deposit requires a deep study to achieve a better understanding of the kaolinization process. In this thesis, geology of a newly discovered kaolin from eastern Kinta Valley, Malaysia were explored through outcrop investigation and geochemical analyses. The kaolin was also characterized in term of its chemical and mineral composition, plus the textural, physical, chemical, thermal and ceramic properties to evaluate its potential for industrial application. Characterized techniques included PSD, FESEM, S.G., atterberg limits, colour measurement, XRD, FTIR, XRF, DTA/TG and fired properties (firing shrinkage, water adsorption, modulus of rupture), and the results were compared to reference sample from an established deposit (Bukit Lampas). Geological study suggests that the kaolin is derived from hydrothermal alteration of leucocratic microgranite, and the kaolinized granite consists almost entirely of quartz and kaolin minerals with extremely low content of alkali and tinaniaferrous bearing phases. Characterization of the washed clay had found that it is the typical soft kaolin which may have halloysite substituted for the fine platy kaolin in the clay fraction. The kaolin has moderate moulding properties but superior optical and refractory properties, thus ideal for production of whiteware or porcelain which demands extreme brightness and whiteness. This study presents a new mode of kaolin occurrence in Malaysia with potential to be developed into a new kaolin mining region.